2021
DOI: 10.1101/gr.276137.121
|View full text |Cite
|
Sign up to set email alerts
|

Gene by environment interaction mouse model reveals a functional role for 5-hydroxymethylcytosine in neurodevelopmental disorders

Abstract: Mouse knockouts of Cntnap2 exhibit altered neurodevelopmental behavior, deficits in striatal GABAergic signaling and a genome-wide disruption of an environmentally sensitive DNA methylation modification (5-hydroxymethylcytosine, 5hmC) in the orthologs of a significant number of genes implicated in human neurodevelopmental disorders. We tested adult Cntnap2 heterozygous mice (Cntnap2+/-, lacking behavioral or neuropathological abnormalities) subjected to a prenatal stress and found that prenatally stressed Cntn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 89 publications
(128 reference statements)
1
13
0
Order By: Relevance
“…In a more recent paper by Papale et al ( 2022 ), the brain tissue of ASD mouse models ( Cntnap2 ) that were projected to prenatal stress was tested. The sample lacked behavioral or neuropathological abnormalities.…”
Section: Resultsmentioning
confidence: 99%
“…In a more recent paper by Papale et al ( 2022 ), the brain tissue of ASD mouse models ( Cntnap2 ) that were projected to prenatal stress was tested. The sample lacked behavioral or neuropathological abnormalities.…”
Section: Resultsmentioning
confidence: 99%
“… Dams were exposed from GD 15–2 to a schedule of repeated variable stress, including restraint stress with or without light, and forced swim ( Ben Hamida et al, 2022 ). From GD 12–18, dams were exposed to variable stress, including constant lighting, restraint stress, exposure to fox odor, exposure to novel objects, exposure to novel noise, cage changes, and saturated bedding ( Papale et al, 2022 ). From GD 14–21, dams were exposed to a repeating schedule of restraint stress, wet bedding, cage changes, and exposure to novel objects ( Petroni et al, 2022a , b ).…”
Section: Prenatal Stressmentioning
confidence: 99%
“…From GD 12–18, dams were exposed to variable stress, including constant lighting, restraint stress, exposure to fox odor, exposure to novel objects, exposure to novel noise, cage changes, and saturated bedding ( Papale et al, 2022 ).…”
Section: Prenatal Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Gene by environment interactions have also been explored in rodent models. One study in mice found that Cntnap2 heterozygotes exposed to prenatal stress displayed altered sociability similar to Cntnap2 knockouts, indicating a gene by environment interaction in neurodevelopment disorders ( Papale et al, 2022 ). Another study examined genetic and environmental factors in impaired social and communication skills in mice, showing that the Nlgn3/Cyfip1 pathway plays a role in shaping behavior and is influenced by the social environment ( Sledziowska et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%